(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To compare the functional outcome of double Peroneus Longus with Quadrupled Hamstring in primary isolated Anterior Cruciate Ligament Reconstruction(ACL) Methods: This randomized trial was conducted in Orthopaedic department Allied Hospital Faisalabad from 23rd March 2015 to 23rd March 2020.All adults patients with ACL tear fulfilling the inclusion criteria were randomly and equally divided into group A( double Peroneus Longus ) and group B( Quadrupled Hamstring) and operated arthroscopically.Post operative functional outcome was assessed with Tegner-Lysholm score and International Knee Documentation Committee (IKDC) and American Orthopaedic Foot and Ankle Society Score(AOFAS) at 12th months follow up and compared with pre operative values. P value was calculated with paired t test for statistical significance. P value < 0.05 was considered significant. Results: A total of 62 patients were enrolled in this study but 56 completed the study. Both group A and B had 28 patients each. Male patients were 26( 92.85%) in group A and 27( 96.42%) in group B. Female patients were 2(7.14% ) in group A and 1( 3.57%) in group B. The mean age of group A was 39.4±6 years and group B 39.6±2 years. Right ACL was ruptured in 17(60.71% ) in group A and 19(67.85% ) in group B. The mean Tegner-Lysholm score improved from preoperative 69.1 + 2.9 to post operative 92.2 + 2.5 at 12 months in group A while in group B it improved from 70.5 + 1.5 to 91.4 + 1.7(P >0.05).The mean IKDC score improved from 40.7±3 to 91.4±1 in group A while group B had pre operative IKDC score of 42.5±5 and improved to 92.7±3(P >0.05) at 12 months. The mean pre-operative AOFAS score of group A was 100 and post-operative score was 98.4 ± 2.1(P >0.05). Conclusion: Both double Peroneus Longus autograft and Quadrupled Hamstring was effective in treating ACL reconstruction. No statistically significant difference however was noted in the functional outcome of double Peroneus Longus autograft when compared with Quadrupled Hamstring for primary Anterior Cruciate Ligament Reconstruction(ACL) at 12 months follow up.